2018
DOI: 10.1108/mrr-01-2017-0005
|View full text |Cite
|
Sign up to set email alerts
|

A new insight into alumni satisfaction model for Islamic higher education institutions (IHEI)

Abstract: Purpose The purpose of this study is to explore and decompose a satisfaction model using alumni’s perspective for Islamic-based higher education institutions (IHEI) with the antecedent of perceived quality and value and the consequence of loyalty. Design/methodology/approach A study was used, using 44-item, a ten-point Likert-scale questionnaire administered to 360 alumni from various classes started from the 1970s till 2000s. Theoretical-based, national qualification framework of Indonesian higher education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 107 publications
0
6
1
Order By: Relevance
“…The factors considered in this group were greetings and salam in Islam. This is different with the study of Rafik and Priyono, 16 who is finding that the presence of good environment and Islamic value embodiment supporting learning programs on campus is the most significant trigger for the knowledge development.…”
Section: Discussioncontrasting
confidence: 76%
“…The factors considered in this group were greetings and salam in Islam. This is different with the study of Rafik and Priyono, 16 who is finding that the presence of good environment and Islamic value embodiment supporting learning programs on campus is the most significant trigger for the knowledge development.…”
Section: Discussioncontrasting
confidence: 76%
“…The type of this research is literature review research by finding reference theories that are relevant to the case or problem found [13]. The theoretical references obtained by the study of literature studies serve as the basic foundation and the main tool for Advances in Social Science, Education and Humanities Research, volume 390 further research practice in more depth.…”
Section: Methodsmentioning
confidence: 99%
“…During this time, the internalization of Islamic values is commonly realized in Islamic banking research (Othman and Owen, 2001;Asnawi et al, 2019), tourism and hospitality (Gayatri and Chew, 2013;Eid and El-Gohary, 2015). The dimensions of internalization of Islamic values are also called Islamic values-embodiment (Rafik and Priyono, 2018) and Islamic environment (Abidin, 2015). Empirical findings prove that the implementation of sharia values in service companies determines the overall assessment of service quality perceived by customers (Gayatri et al, 2011;Abidin, 2015;Asnawi et al, 2019).…”
Section: Effect Of Islamic Higher Education Service Quality Dimensions On Perceived Service Qualitymentioning
confidence: 99%
“…In the context of Islamic higher education (IHE), efforts to maintain and expand market share through the implementation of quality services in accordance with Islamic culture are urgently needed to provide practical solutions for organizational managers (Ganguli and Roy, 2011). The dimensions of service quality that are relevant in HE institutions are still debated and become interesting studies in the literature (Rafik and Priyono, 2018) because perceived service quality is highly dependent on customer values and trust that always changes from one culture to another (Furer et al, 2000). So, there is a close relationship between culture and service quality perception (Jabnoun and Khalifa, 2005).…”
Section: Introductionmentioning
confidence: 99%